Combined radiation therapy and sunitinib for preoperative treatment of soft tissue sarcoma - Jakob, Jens; Simeonova-Chergou, Anna; Kasper, Bernd; Ronellenfitsch, Ulrich; Wenz, Frederik; Hohenberger, Peter (Annals of surgical oncology, 2015)
Background: Antiangiogenic substances and radiation therapy (RT) may have synergistic effects and improve irradiation efficacy. We present a cohort study evaluating the toxicity of combined sunitinib and RT as neoadjuvant treatment of extremity and retroperitoneal soft tissue sarcoma (STS). Methods: Sixteen patients with locally advanced extremity (6/16) or retroperitoneal (10/16) STS were treated with continuous-dosing sunitinib (15/16: 37.5 mg daily; 1/16: 25 mg daily) and standard RT (45-50.4 Gy) preoperatively. Surgery was scheduled 5-9 weeks following neoadjuvant treatment. The primary goal of the study was to determine combined treatment toxicity according to the Common Terminology Criteria for Adverse Events. Secondary goals were the evaluation of postoperative morbidity and treatment response. Results: Eight of 16 patients developed grade 3, and one patient developed grade 4, hematological toxicity. One patient experienced grade 3 hand-foot syndrome. The most frequent treatment toxicities of any grade were hematological (15/16) or dermatological (9/16). Three patients had partial response, 11 had stable disease, and 2 had progressive disease according to Response Evaluation Criteria in Solid Tumors (RECIST). Fourteen of 16 patients underwent surgery; tumors were not removed in two patients because of patient refusal or intercurrent metastatic disease. The proportion of tumor necrosis exceeded 90 % in 5 of 14 patients, and 4 patients had postoperative complications requiring reintervention. Conclusions: Preoperative treatment with concurrent sunitinib and RT was tolerable, and postoperative morbidity did not increase. Combined treatment with RT and sunitinib was also feasible in patients with retroperitoneal STS, and warrants further investigation.